Clinical outcomes in relapsed oropharyngeal cancer after definitive (chemo) radiotherapy. (27th August 2021) - De Felice, Francesca; Bird, Thomas; Michaelidou, Andriana; Jeannon, Jean‐Pierre; Simo, Ricard; Oakley, Richard; Lyons, Andrew; Fry, Alastair; Cascarini, Luke; Asit, Arora; Thavaraj, Selvam; Reis Ferreira, Miguel; et al.
Abstract: Objectives: To report clinical outcomes of relapsed oropharyngeal squamous cell carcinoma (OPSCC) after definitive intensity‐modulated (chemo)radiotherapy [(C)RT]. Materials and methods: Data for all relapsed patients treated for OPSCC with definitive (C)RT between 2010 and 2016 were collected. Primary end‐point was post‐failure survival (PFS). Results: Overall, 273 OPSCC patients completed definitive (C)RT. Of these, 42 cases ( n  = 26 human papilloma virus (HPV)‐negative; n  = 16 HPV‐positive) had relapsed ( n  = 23 persistent disease; n  = 19 recurrent disease) and were included in the final analysis. Two‐year PFS for the entire population was 30.6%; 20.5% for HPV‐negative and 43.8% for HPV‐positive patients. Salvage curative surgery was associated with a significantly higher 2 years PFS rate (56.2%) compared with palliative treatment (22.9%) and best supportive care (0%) ( p  < 0.001). A positive trend in 2 years PFS was recorded in the early complete response cases (49.5%) versus patients who did not achieve a complete response within 3 months of the end of (C)RT (23.0%) ( p  = 0.11). Conclusion: A higher PFS rate is achieved when relapsed OPSCC cases are treated with salvage curative intent. HPV‐positive disease and early complete response within 3 months from the end of (C)RT may be related to better PFS.